Projeto de climatização do novo auditório da UFPA campus de Tucuruí com base no método de cálculo de carga térmica residencial - FRANÇA, Welington Lopes de (2022)
A good air conditioning project is important due to the constant increase of energy demand, be them nationally and internationally, in addition, studies show that thermal comfort is directly connected to the individual's productivity, whether in the work place or in daily activities. So, the main objective was analyzed the thermal load parcels of the new auditorium of the Federal University of Pará, campus of Tucuruí, that will be the site of the most diverse events at the university, with a space of approximately 198 m2 and capacity for 180 people. In order to accommodate the occupants thermally comfortable, it was analyzed using the CLTD (Cooling Load Temperature Differences) methodology introduced by ABNT NBR 16655-3: 2019 as thermal load portions referring to insolation on the walls and windows, in addition to the loads related to people, equipment and due to air infiltration. Based on the results found, the total thermal demand of 200 kBtu/h where almost 50% of this value represents the load due to the presence of people, followed by the thermal load due to infiltration on the cracks of the doors and window which represents 24% of the total. In accordance these values, were selected to supply the thermal loads five air-conditioners were selected three with capacity of 36000 Btu/h and two with capacity of 47000 Ktu/h, three of them of the high wall inverter model and two of the “piso-teto” model, also inverter.